2019
DOI: 10.3389/fimmu.2019.01762
|View full text |Cite
|
Sign up to set email alerts
|

The Sweet-Side of Leukocytes: Galectins as Master Regulators of Neutrophil Function

Abstract: Among responders to microbial invasion, neutrophils represent one of the earliest and perhaps most important factors that contribute to initial host defense. Effective neutrophil immunity requires their rapid mobilization to the site of infection, which requires efficient extravasation, activation, chemotaxis, phagocytosis, and eventual killing of potential microbial pathogens. Following pathogen elimination, neutrophils must be eliminated to prevent additional host injury and subsequent exacerbation of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 197 publications
1
30
0
1
Order By: Relevance
“…Glycans also play crucial and multifaceted roles in B cell and T cell differentiation via cell-surface or secreted proteins, including selectins, galectins, and siglecs, which can further connect SARS-CoV-2 to immune response and immune regulation (27). In particular, the complex N-glycans are ligands for galectins, which are able to engage different glycoproteins to regulate immune cell infiltration and activation upon virus infection (33,34). These mechanisms underlying SARS-CoV-2 infection and spread are worth further clarification based on a detailed analysis of clinical characteristics in humoral and cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Glycans also play crucial and multifaceted roles in B cell and T cell differentiation via cell-surface or secreted proteins, including selectins, galectins, and siglecs, which can further connect SARS-CoV-2 to immune response and immune regulation (27). In particular, the complex N-glycans are ligands for galectins, which are able to engage different glycoproteins to regulate immune cell infiltration and activation upon virus infection (33,34). These mechanisms underlying SARS-CoV-2 infection and spread are worth further clarification based on a detailed analysis of clinical characteristics in humoral and cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Galectins are another key family of GBPs implicated in virtually all aspects of the immune system (Brinchmann et al, 2018;Elola et al, 2018;Robinson et al, 2019). Galectins are expressed in many cell types including those of squamous epithelia, gastrointestinal tract, adipocytes, immune cells, and even erythrocytes (Thiemann and Baum, 2016).…”
Section: Galectinsmentioning
confidence: 99%
“…On the other hand, protein glycosylation can also facilitate immune response by sensor molecules or antibodies specific for glycan recognition. N-glycans are known ligands for galectins, which triggers inflammation events such as cytokine release, immune cell infiltration (Robinson et al, 2019; Wang et al, 2019), of which may contribute to the HCoV-19 pathogenesis and correlated with the disease severity. Moreover, epidemiological studies have shown that ABO polymorphism are linked to different susceptibility to both HCoV-19 and SARS-CoV infections (Cheng et al, 2005; Zhao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%